Effects of spontaneous first breath on placental transfusion in term neonates born by cesarean section: A randomized controlled trial - Kilicdag, Hasan; Parlakgumus, Deniz; Demir, Suleyman Cansun; Satar, Mehmet (Frontiers in Pediatrics, 2022)
Abstract Background: The role of umbilical cord management in placental transfusion in cesarean section (CS) requires clarification. Spontaneous first breath may be more important than the timing of cord clamping for placental transfusion in neonates born by CS. Objective: This study aimed to evaluate the impact of cord clamping after the first spontaneous breath on placental transfusion in neonates born by CS. Methods: We recruited women with a live singleton pregnancy at ≥37.0 weeks of gestation admitted for CS. The interventions performed, including physiologic-based cord clamping (PBCC), intact-umbilical cord milking (I-UCM), 30 s delay in cord clamping (30 s DCC), and 60 s delay in cord clamping (60 s DCC), were noted and placed in a sealed and numbered envelope. The sealed envelope was opened immediately before delivery to perform randomization Results: A total of 123 infants were eligible for evaluation. Of these, 31, 30, 32, and 30 were assigned to the PBCC, I-UCM, 30 s DCC, and 60 s DCC groups, respectively. The mean hemoglobin (Hb) and hematocrit (Hct) were significantly higher in the 60 s DCC group than in the PBCC group (p = 0.028 and 0.019, respectively), but no difference was noted among the I-UCM, 30 s DCC, and PBCC groups at 36 h of age. Further, no significant differences were observed in the mean Hb and Hct among the I-UCM, 60 s DCC, and 30 s DCC groups. Peak total serum bilirubin levels were higher in the 60 s DCC group than in the I-UCM and PBCC groups (p = 0.017), but there was no difference between the 60 s DCC and 30 s DCC groups during the first week of life. Conclusions: Our findings demonstrated that PBCC, 30 s DCC, and I-UCM in neonates born by CS had no significant differences from each other on placental transfusion. The Hb and Hct in the neonates were higher after 60 s DCC than after PBCC.